1981
DOI: 10.1007/bf00384094
|View full text |Cite
|
Sign up to set email alerts
|

Expression of storage-protein genes during soybean seed development

Abstract: Mature seeds of Glycine max (L.) Merr. contain two major storage proteins, a glycosylated 7S protein (conglycinin) and a non-glycosylated 11S protein (glycinin). Accumulation of these proteins and their mRNAs during seed development in cv. Provar was studied by SDS polyacrylamide gel electrophoresis and by "Northern" (DNA-RNA) hybridization. The 11S acidic and basic subunits and the 7S α' and α subunits began to accumulate 18-20 d after pollination, shortly after the termination of cell division in developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
173
3
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 34 publications
11
173
3
1
Order By: Relevance
“…4A). MIPS transcript was observed in cotyledons at the earliest developmental stages analyzed, 0 to 2 mm (corresponding in size up to approximately stage C; Meinke et al, 1981). Maximal levels of MIPS RNA were observed in 2-to 4-mm seeds (equivalent to stages D-F; Fig.…”
Section: Soybean Mips Rna Expressionmentioning
confidence: 83%
See 1 more Smart Citation
“…4A). MIPS transcript was observed in cotyledons at the earliest developmental stages analyzed, 0 to 2 mm (corresponding in size up to approximately stage C; Meinke et al, 1981). Maximal levels of MIPS RNA were observed in 2-to 4-mm seeds (equivalent to stages D-F; Fig.…”
Section: Soybean Mips Rna Expressionmentioning
confidence: 83%
“…Immature seed samples were grouped by developmental stages as described previously (Meinke et al, 1981). Stages collected included: E ϭ 2.6 to 3.4 mm, F ϭ 3.6 to 4.4 mm, G ϭ 4.6 to 5.4 mm, H ϭ 5.6 to 6.4 mm, I ϭ 6.6 to 7.4 mm, J ϭ 7.6 to 8.4 mm, K ϭ 8.6 to 9.4 mm, and L ϭ 9.6 to 10.4 mm.…”
Section: Protein Expression and Immunoblot Analysesmentioning
confidence: 99%
“…In each case the expression was earlier in the development of transgenic tobacco embryos than expected from previous reports. Soybean P-conglycinin genes (a', a, and P subunits) are highly expressed in soybean embryos in midto late-maturation stages (Meinke et al, 1981;Walling et al, 1986). In situ hybridization analysis of P-conglycinin expression (both a' and / 3 subunit mRNAs hybridized to the probe) showed no expression in globular-, heart-, or cotyledon-stage soybean embryos (Perez-Grau and Goldberg, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This sunbean experiment showed that gene cloning and Agrobacterium tumefaciens transformation techniques could be combined to transfer foreign genes into plant cells and study their function. Research in several laboratories with legume seed protein genes, such as b-conglycinin, glycinin, Kunitz trypsin inhibitor, and lectin, showed that their mRNA accumulation patterns are regulated temporally and spatially (Goldberg et al, 1981a(Goldberg et al, , 1983Meinke et al, 1981;Rerie et al, 1992) and controlled by both transcriptional and posttranscriptional processes (Evans et al, 1984;Beach et al, 1985;Chappell and Chrispeels, 1986;Walling et al, 1986). Subsequent work determined that cisregulatory sequences flanking legume seed protein genes could confer embryo-specific expression patterns in heterologous plants, such as tobacco (Nicotiana tabacum) and petunia (Petunia hybrida; Chen et al, 1986;Okamuro et al, 1986;Jofuku et al, 1987;Higgins et al, 1988;Naito et al, 1988;Baumlein et al, 1992;Wohlfarth et al, 1998;Chandrasekharan et al, 2003).…”
Section: Legumes Have Been Used To Study Seed Development For More Thmentioning
confidence: 99%